2020
DOI: 10.1139/cjfas-2019-0146
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of interannual variability in long-term aquatic ecological surveys

Abstract: Long-term ecological surveys (LTES) often exhibit strong variability among sampling dates. The use and interpretation of such interannual variability is challenging due to the combination of multiple processes involved and sampling uncertainty. Here, we analysed the interannual variability in ∼30 years of 150 species density (fish and invertebrate) and environmental observation time series in four aquatic systems (stream, river, estuary, and marine continental shelf) with different sampling efforts to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Many previous studies have attempted to interpret interannual variability in juvenile salmonid abundance solely in relation to environmental drivers (Blum, Kanno, & Letcher, 2018; Cauvy‐Fraunié et al, 2019; Jensen & Johnsen, 1999; Lobón‐Cerviá, Rasmussen, & Mortensen, 2017). This potentially results in erroneous attribution of processes, or for environmental effects to go undetected due to apparently high levels of noise in recruitment data that is associated with temporally varying stock levels.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have attempted to interpret interannual variability in juvenile salmonid abundance solely in relation to environmental drivers (Blum, Kanno, & Letcher, 2018; Cauvy‐Fraunié et al, 2019; Jensen & Johnsen, 1999; Lobón‐Cerviá, Rasmussen, & Mortensen, 2017). This potentially results in erroneous attribution of processes, or for environmental effects to go undetected due to apparently high levels of noise in recruitment data that is associated with temporally varying stock levels.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the dynamics of invertebrate trends are difficult to capture and model over the long term due to high interannual variation that is inherent across these taxa (Baranov et al, 2020 ; Cauvy‐Fraunié et al, 2020 ); this appears to also be the case with our data, shown in figures 2 and 3 . We have chosen to model long‐term abundance change of macroinvertebrates using hierarchical linear modelling, and while this approach allows us to provide our best estimate of how abundance has changed on average since 2002, the models presented do not capture changes from 1 year to the next, nor explain occasional short‐term non‐linear patterns in geometric means.…”
Section: Discussionmentioning
confidence: 51%
“…Although we discuss family-level trends in the context of water quality changes (due to different families varying in response to water quality improvement and pollution), within families there is also variation among species in their sensitivity to water quality metrics, or their 'saprobic index', which we were not able to capture in this analysis (Metcalfe, 1989). Finally, the dynamics of invertebrate trends are difficult to capture and model over the long term due to high interannual variation that is inherent across these taxa (Baranov et al, 2020;Cauvy-Fraunié et al, 2020); this appears to also be the case with our data, shown in figures 2 and 3. We have chosen to model long-term abundance change of macroinvertebrates using hierarchical linear modelling, and while this approach allows us to provide our best estimate of how abundance has changed on average since 2002, the models presented do not capture changes from 1 year to the next, nor explain occasional short-term non-linear patterns in geometric means.…”
Section: Limitations and Caveatsmentioning
confidence: 94%
See 1 more Smart Citation
“…Temporal variation (i.e., year-to-year variation) in ecological conditions (e.g., prey availability and species interactions) may impose an important limitation in recognising meaningful conclusions about biological processes like feeding when studies are projected on short-time scale designs. More specifically, interannual variability might drive ecological research focused on short-term studies towards less reliable conclusions compared to studies conducted on a longer term (Purdom et al 2015;Cauvy-Fraunié et al 2020). In addition, a practical issue with ontogenetic niche shift studies is that the diversion of a population sample into ontogenetic subgroups often possesses a problem with respect to low sample sizes for some of the subgroups.…”
Section: Introductionmentioning
confidence: 99%